MODELING OF EDUCATIONAL PROCESS OF HIGH EDUCATIONAL INSTITUTION IN THE EDUCATIONAL AND INFORMATIONAL ENVIRONMENT - Рахманов, В. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article deals with the interaction of different models of educational process of high educational institution. This allows you to optimize the organization of the educational process high educational institution. Using the properties of the educational and information environment provides a new quality of all the work of the tutor and student: professional behavior is formed, accumulates the highest levels of focus, knowledge and readiness for action; advanced knowledge becomes a tool for self-analysis and self-manifestation of reserves; a high level of skills promotes self-revelation of the person, and the improvement of educational technology - Search result. Organization of productive interaction of the tutor and students, using the properties of educational and information environment, contributes to the effectiveness of the educational process in the high educational institution, creating conditions for self-realization, self-determination of the student's personality, the creative potential of the individual, the formation of value orientations and moral qualities and their subsequent updating in the profession